Comparative Proteomic Analysis of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) Tropical and Temperate Lineages: Uncovering Differences During Ehrlichia canis Infection - Sanches, Gustavo Seron; Villar, Margarita; Couto, Joana; Ferrolho, Joana; Fernández de Mera, Isabel G.; André, Marcos Rogério; Barros-Battesti, Darci Moraes; Machado, Rosangela Zacarias; Bechara, Gervásio Henrique; Mateos-Hernández, Lourdes; de la Fuente, José; Antunes, Sandra; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The tick vector Rhipicephalus sanguineus is established as a complex of closely related species with high veterinary-medical significance, in which the presence of different genetic, morphological, and biological traits has resulted in the recognition of different lineages within taxa. One of the most striking differences in the “temperate” and “tropical” lineages of R. sanguineus (s.l.) is the vector competence to Ehrlichia canis, suggesting that these ticks tolerate and react differently to pathogen infection. The present study addresses the SG and MG proteome of the R. sanguineus tropical and temperate lineages and compares their proteomic profile during E. canis infection. Batches of nymphs from the two lineages were allowed to feed on naïve and experimentally E. canis infected dogs and after molting, adults were dissected, and salivary glands and midgut tissues separated. Samples were screened for the presence of E. canis before proteomic analyses. The representation of the proteins identified in infected and non-infected tissues of each lineage was compared and gene ontology used for protein classification. Results highlight important differences in those proteomic profiles that added to previous reported genetic, biological, behavioral, and morphological differences, strengthening the hypothesis of the existence of two different species. Comparing infected and non-infected tissues, the results show that, while in midgut tissues the response to E. canis infection is similar in the salivary glands, the two lineages show a different pattern of protein representation. Focusing on the proteins found only in the infected condition, the data suggests that the cement cone produced during tick feeding may be implicated in pathogen infection. This study adds useful information to the debate on the controversial R. sanguineus systematic status, to the discussion related with the different vectorial competence occurring between the two lineages and identifies potential targets for efficient tick and tick-borne disease control.